The adaptation of French expatriate executives in Morocco: thematic analysis - Ghita; Oumaima RHAZAOUI; Ahmed MAGHNI (Moroccan Journal of Quantitative and Qualitative Research, 2025)
Globalization has encouraged companies to establish themselves abroad, which has resulted in the expatriation of managers. In Morocco, the adaptation of French expatriates is crucial for their success. This qualitative study interviewed 17 French expatriates working in various sectors in Morocco. The results allowed to discuss the determinants of adaptation, both organizational, contextual and individual, as well as its positive and negative implications on the work, life and personality of French expatriates.